The Application of Accounting Methodology of Radar Charts to Analyze the Sector of Sawmilling and Planning of Wood of Austria. - Benedito, Miguel Angel Pérez (Archives of Business Research, 2015)
The accounting methodology of radar charts (AMRCh) explains the behavior of companies through average periods of maturation of management activity on short term. These variables represented on each one of axes of radar chart allow measure the activity of companies, applying the cosine and sine theorems of plane geometry. The analysis of activity is for each one of areas represented on a radar chart through by non-slanted indicators. This study shows that frontier effect carry out companies to adopt a sectorial management to maintain their activity. This manuscript presents the basic theory of AMRCh, firstly. Secondly, the study analyzes the management of industrial sector, which carries the research to the evaluation of the location of companies by the frontier effect. The manuscript concludes that a company adopts a management strategy according to trade conditions of industrial sector.